Strategic Collaborative Quality Management and Employee Job Satisfaction - Ali Mohammad Mosadeghrad (Kerman University of Medical Sciences, 2014)
Background This study aimed to examine Strategic Collaborative Quality Management (SCQM) impact on employee job satisfaction. Methods The study presents a case study over six years following the implementation of the SCQM programme in a public hospital. A validated questionnaire was used to measure employees' job satisfaction. The impact of the intervention was measured by comparing the pre-intervention and post-intervention measures in the hospital. Results The hospital reported a significant improvement in some dimensions of job satisfaction like management and supervision, organisational policies, task requirement, and working conditions. Conclusion This paper provides detailed information on how a quality management model implementation affects employees. A well developed, well introduced and institutionalised quality management model can improve employees' job satisfaction. However, the success of quality management needs top management commitment and stability.